The Effect of Financial Compensation in Increasing Employee Motivation and Performance (Case Study of Security Guards at Trunojoyo University, Madura) - Putri Azizah Fitriyah Maharani; Bagus Alamsyah Bahari; Hikmatul Maghfiroh; Iriani Ismail (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research aims to determine the effect of financial compensation in increasing employee motivation and performance, this was done as an effort to improve employee performance. In this research, descriptive qualitative methods were used using probability sampling and random sampling techniques. The research population consisted of all 150 Trunojoyo Madura University (UTM) security guards and 7 people were selected as samples with 3 people as key sources and the others as supporters. Research data was obtained by going directly to the field and interviewing selected sources. The data analysis used was interactive analysis and data triagulation. It was found that financial compensation has a direct effect on employee work motivation because the initial goal of a person's work is salary, financial compensation also has an effect on employee performance because it builds motivation